Learning spaces in higher education: A systematic literature review - Nicolaou, Anna; Christou, Eirini; Parmaxi, Antigoni; Pashia, Eleni (My University, 2023)
The rapid advancement of technology has been transforming the way our environments and processes within them have been traditionally perceived and developed. This paper focuses on learning environments in order to explore through a systematic review, the way learning spaces in Higher Education are framed by different theories and the types of learning spaces discussed in literature – mainly physical, virtual and hybrid – as well as the way they are used alongside affordances and challenges they bring with them. The paper, finally, concludes with a collection of design guidelines for practitioners and designers of learning spaces in Higher Education.